2020
DOI: 10.1016/s1474-4422(20)30219-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fluoxetine on functional recovery after acute stroke (EFFECTS): a randomised, double-blind, placebo-controlled trial

Abstract: BACKGROUNDPrevious studies have suggested that fluoxetine could improve neurological recovery after stroke. The EFFECTS trial was designed to test the hypothesis that administration of fluoxetine for 6 months after acute stroke would improve functional outcome. METHODSEFFECTS was an investigator-led, parallel group, randomised, placebo-controlled trial that enrolled non-depressed stroke patients aged 18 years or older between two and 15 days after stroke onset in 35 hospitals in Sweden. The patients had a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 26 publications
7
134
1
8
Order By: Relevance
“…In our study, one female receiving fluoxetine had a bone fracture, compared to no fractures in the placebo group. This is consistent with previous trials which also reported more frequent bone fractures in patients taking SSRIs [9][10][11]25] and confirms the findings from observational studies [26].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, one female receiving fluoxetine had a bone fracture, compared to no fractures in the placebo group. This is consistent with previous trials which also reported more frequent bone fractures in patients taking SSRIs [9][10][11]25] and confirms the findings from observational studies [26].…”
Section: Discussionsupporting
confidence: 92%
“…Two patients taking fluoxetine in our cohort required an additional dose of fluoxetine or a new antidepressant medication, compared to four in the placebo group. This is consistent with large trials evaluating the benefit of six months of fluoxetine administration, which have also reported that patients given fluoxetine were less likely than those given a placebo to have developed new depression at six months [9][10][11].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations